2001
DOI: 10.1093/jn/131.11.2936
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Derived from Bovine β-Casein Modulates Functional Properties of Bone Marrow-Derived Macrophages from Germfree and Human Flora-Associated Mice

Abstract: The purpose of this study was to evaluate the immunomodulatory activity of a peptide derived from bovine beta-casein (beta-CN), the beta-CN (193-209) peptide, on mouse macrophages that were obtained either from germfree (GF) or from human flora-associated (HF) mice. Macrophages were derived from bone marrow (BMDM) in the presence of recombinant macrophage colony-stimulating factor and exposed to the peptide or lipopolysaccharide (LPS). Membrane marker expression [F4/80, Mac-1, major histocompatibility complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…However, the Arg residue at the N-or C-terminal region of a peptide Recio and Visser (1999) b (bovine) 193-209 YQEPVLGPVRGPFPIIV Sandre et al (2001) has been suggested to be the leading motif recognizable by specific surface membrane receptors; in this context, it is worth noting that the immunomodulatory ACEinhibitor peptide b-casokinin-10 (among other ACEinhibitory peptides) has Arg in its C-terminus. Opioid peptides are also thought to affect the immunoreactivity of lymphocytes via opiate m-receptors, which, for endorphins, are present on T-lymphocytes and human phagocytic leucocytes (Meisel, 1998).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Arg residue at the N-or C-terminal region of a peptide Recio and Visser (1999) b (bovine) 193-209 YQEPVLGPVRGPFPIIV Sandre et al (2001) has been suggested to be the leading motif recognizable by specific surface membrane receptors; in this context, it is worth noting that the immunomodulatory ACEinhibitor peptide b-casokinin-10 (among other ACEinhibitory peptides) has Arg in its C-terminus. Opioid peptides are also thought to affect the immunoreactivity of lymphocytes via opiate m-receptors, which, for endorphins, are present on T-lymphocytes and human phagocytic leucocytes (Meisel, 1998).…”
Section: Article In Pressmentioning
confidence: 99%
“…The immunomodulatory peptide derived from bovine b-casein, viz. f193-209, was shown to enhance the antimicrobial activity of mouse macrophages, which had been obtained either from germ-free or from human floraassociated mice, without proinflammatory effects (Sandre et al, 2001).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…This peptide displays immunomodulatory properties and shows mitogenic activity on primed lymph node cells and unprimed rat spleen cells [9]. It manifests chemotactic activity on L14 lymphoblastoid cell line [10], and enhances phagocytosis in rat macrophages [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been known for some time that milk contains proteins that are biologically active or possess bioactive peptides encrypted within their primary sequence that can be released upon hydrolysis (Clare & Swaisgood, 2000;Schanbacher, Talhouk, & Murray, 1997). The bioactive proteins and peptides derived from milk have been reported to modulate functions of the gastrointestinal tract including an increased gastrointestinal transit time, antidiarrhoeal activity by enhancing water and electrolyte adsorption, vasoregulatory responses, providing nonimmune disease defense and control of microbial infection (Aniansson, Andersson, Lindstedt, & Svanborg, 1990;Clare & Swaisgood, 2000;Daniel, Vohwinkel, & Rehner, 1990;Meisel & Schlimme, 1990;Stromqvist et al, 1995;Schanbacher et al, 1997;Sandre et al, 2001;Silva & Malcata, 2005).…”
Section: Introductionmentioning
confidence: 99%